The World almanac and book of facts : 2000. (New Jersey : World Almanac Books, 2000)
For more than 130 years, The World Almanac has set the standard for annual yearbooks, delivering comprehensive, easy-to-use information and tables on a score of topics. For lovers everywhere of trivia, crosswords, and factoids, this is the bible. A perennial best-seller -- and second only to Poor Richard's Almanack for the all-time crown -- the 2000 edition of The World Almanac is a thorough (and thoroughly enjoyable) snapshot of the world of the dawn of a new millennium.
Keywords: Almanacs, American -- Statistics